Collection 1992 : Richard Baquié - Marie José Burki - Sophie Calle - Alan Charlton - Dan Graham - Louis Jammes - Ange Leccia - Musée Khombôl - Jean-Luc Parant - Laurent Pariente - Françoise Quardon - Krzysztof Wodiczko - James Turrell. (Lyon : Musée d'Art Contemporain, 1992)
Richard Baquié - Marie José Burki - Sophie Calle - Alan Charlton - Dan Graham - Louis Jammes - Ange Leccia - Musée Khombôl - Jean-Luc Parant - Laurent Pariente - Françoise Quardon - Krzysztof Wodiczko - James Turrell
Collection 1992, Musée d'Art Contemporain, Lyon, 1992
boek